Influences of the Cultural Revolution on the education and wages of today's Chinese laborers. Issue 1 (1st January 2020) - Chou, Li-Chen; Zhang, Wan-Hao; Hu, Zixuan
Abstract: More than 40 years after the end of the Cultural Revolution, does it still affect today's Chinese laborers? In this study, data from the 2012 Chinese General Social Survey are used to investigate the possible differences between the education and wage levels of the laborers of parents who have experienced the Cultural Revolution and others who have not. Empirical results show that the average education and wage levels of laborers whose parents have experienced the Cultural Revolution and attained at least primary education qualifications are significantly lower than other groups in the labor market. We believe that during the Cultural Revolution, the political and social climate lowered the public's recognition of the value of education in society and reduced the incentive for human capital investment.